Implementation and Evaluation of Wireless Networked Control Systems using Modbus - Caldiéri, M. R.; Bigheti, J. A.; Godoy, E. P. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2017)
The recent introduction of wireless transmitters in the industry has driven a new interest in measuring and control techniques, but most applications are restricted to open loop monitoring applications. The reason is the lack of reliability due to problems inherent to the transmission medium, such as loss of information, time varying delays, slow and sometimes-aperiodic update measurements and interference. In order to enable and make the wireless networked control systems (WNCS) more reliable, many control techniques have been researched, including the PIDPlus representing a modified PID algorithm developed for use in systems in which the sampling frequency requirement cannot be guaranteed. This paper presents the implementation of the Modbus protocol for WNCS applications. The Modbus TCP was embedded in dedicated hardware enabling the transmission of data via Ethernet TCP/IP and Wi-Fi. A comparison of PID controllers for the WNCS subjected to variable delays and sampling, and packet losses were done. Experimental results in a pilot plant prove the efficiency of the implementation of a wireless control loop using a Wi-Fi network with embedded Modbus protocol and PIDPlus controller.
Keywords: Modbus TCP/IP; Networked control; PIDPlus; Wireless sensor